Estudo e caracterização da cinza proveniente do caroço do açai despolpado - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The growing generation of residue from industrial and commercial activities has become a major concern for society in recent years. In current models of management and production, the concept of sustainability and / or reuse of waste are increasingly present. One of the sectors that reuse most residue is the Civil Construction, because it uses materials that are often discarded with less market value and because they have characteristics of strength and durability equal to or better than the conventional materials used in the industry. In view of this, it was proposed to study the ash of the açaí’s lump with removal of the polp in the "amassadeiras", in order to evaluate the influence of the burning, grinding degree, temperature and ideal time required to characterize this ash as a material with properties Pozolanics. For this, in the experimental program, samples of açaí seed sacks were collected, due to the need to develop a specific process of ash production with analysis of the different factors that may influence or not the reuse of this residue.
Keywords: Resíduos; Caroço de açaí; Cinza; Pozolana; CNPQ::CIÊNCIAS EXATAS E DA TERRA